Ober die nichtholonome Hyperflache in verallgemeinerten euklidischem Raum - Stiklakytė, L. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. И. Стиклаките. О неголономной гиперповерхности обобщенного евклидового пространства L. Stiklakytė. Apie apibendrintos euklidinės erdvės neholonominį hiperpaviršių